Healing faith: knowledge, learning and social relationships of healers from Araripe plateau, Brazil - Zank, Sofia; Hanazaki, Natalia (Ethnobiology and Conservation, 2016)
We investigated the practice of healing in three rural communities in Brazil (Ceará) to understand the diseases that are treated, the plants known and used, the ways in which knowledge of the blessing practices and medicinal plants is gained, and the relationships among the healers. We interviewed 41 healers, who treat approximately 20 diseases with blessings and know several species of medicinal plants. Six plants are most often associated with blessing. The transmission of knowledge occurs mainly through people who have kinship. The popularity of a healer was not influenced by the number of therapeutic plants known or the number of diseases treated through blessing. In two communities, the best-known healers are also the most sought after by other healers for the exchange of information and blessings. The results of this study can assist in the establishment of public actions aimed at the enhancement and the recognition of blessing practices.